2009
DOI: 10.1038/jhh.2009.68
|View full text |Cite
|
Sign up to set email alerts
|

Haplotype-based case–control study of receptor (calcitonin) activity-modifying protein-1 gene in cerebral infarction

Abstract: Calcitonin gene-related peptide (CGRP) receptor is a complex molecule that consists of calcitonin receptorlike receptor and receptor activity-modifying protein-1 (RAMP1). It was recently reported that RAMP1-deficient mice (RAMP1(À/À)) showed inflammatory responses with a transiently significant increase in serum CGRP levels and proinflammatory cytokines when compared with RAMP1( þ / þ ) mice. The aim of this study was to investigate the relationship between the human RAMP1 gene and cerebral infarction (CI) usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…A significant difference in the RAMP1 single nucleotide polymorphism rs3754701 frequency was identified between Swedish CH patients and controls. Moreover, RAMP1 polymorphisms have previously been suggested to be implicated in both migraine and medication overuse headache [60,61], and the associated SNPs, rs3754701 and rs7590387, are part of a risk haplotype for cerebral infarction reported in a Japanese case-control study [111]. In addition, RAMP1 mRNA expression was shown to be enhanced in primary fibroblasts from CH patients compared to controls [110].…”
Section: Cgrp and Geneticsmentioning
confidence: 89%
“…A significant difference in the RAMP1 single nucleotide polymorphism rs3754701 frequency was identified between Swedish CH patients and controls. Moreover, RAMP1 polymorphisms have previously been suggested to be implicated in both migraine and medication overuse headache [60,61], and the associated SNPs, rs3754701 and rs7590387, are part of a risk haplotype for cerebral infarction reported in a Japanese case-control study [111]. In addition, RAMP1 mRNA expression was shown to be enhanced in primary fibroblasts from CH patients compared to controls [110].…”
Section: Cgrp and Geneticsmentioning
confidence: 89%
“…40 A human study also revealed the relationship between RAMP1 singlenucleotide polymorphisms and the incidence of cerebral infarction. 41 Some human mutations of RAMP3 gene have also been reported. 42 On the other hand, there have been no reports on human RAMP2 gene mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Although no significant association with migraine susceptibility in general and both with and without aura [ 45 ] and with the response to triptans in all the three genotypes under study [ 46 ], the rs7590387G allele and the rs7590387GG genotype have been found to reduce significantly the risk of transformation MOH [ 46 ]. Interestingly, the relationship of this SNP with cerebral infarction has been examined in a Japanese population, suggesting the T-A-C haplotype to represent a genetic marker for cerebral infarction [ 56 ]. Only one study investigating the methylation pattern with regard to CGRP pathway has resulted from the search.…”
Section: Resultsmentioning
confidence: 99%